ANALISIS STRATEGI POLITICAL BRANDING BASUKI TJAHAJA PURNAMA OLEH KOMUNITAS â€œTEMAN AHOKâ€ MELALUI NEW MEDIA - Suparno, Antoni (Economic Faculty, Attahiriyah Islamic University, 2018)
The purpose of this study is to understand the process of Teman Ahok community was formed, the political branding strategy of Basuki Tjahaja Purnama through new media, and their reasons using new media to spread political branding message. The method used was ethnography. Data collected by in-depth interview, observation, and literature study. The results showed, Teman Ahok founding process start from fantasy theme, fantasy chain, fantasy type, to rethorical visions. Political branding strategy used by Teman Ahok is string up brand value and brand culture, then doing segmenting, targeting, and positioning to perform image optimization and build public trust, and then communicate it by buzzing through new media. Teman Ahok using new media because it provides computer mediated communication, new ways of distributing and consuming message, the virtual realities, whole range transformation of media, and interactive communication with public. (AS) Keywords: Political Branding, Teman Ahok, New Media